Disparity in Decisions on Bankruptcy Petitions Based on Cession of a Portion of Receivables: Disparitas Putusan Permohonan Pailit dengan Dasar Cessie atas Sebagian Jumlah Piutang - Farhan Fedhitama, Muhammad; Siti Anisah (Universitas Islam Indonesia, 2023)
Applications for a declaration of bankruptcy on the basis of cessie for some of the receivables result in different decisions from commercial courts. There are decisions that grant the application and there are also decisions that reject the application. The occurrence of different decisions on bankruptcy applications on the same basis results in a lack of legal certainty. This research aims to examine, analyze and explain the disparity between commercial courts in deciding bankruptcy applications on the basis of cessie for a portion of the receivables. Types of normative legal research with a statutory approach and a concept approach. Data collection techniques were carried out using library research. The data obtained will be analyzed qualitatively. The results of the research conclude, first, that there is a disparity in decisions regarding applications for declaring bankruptcy based on cessie for some of the amounts receivable due to differences in interpretation by judges in interpreting the law. Second, an effort to create legal certainty in a bankruptcy petition based on a cessie for a portion of the receivables is by making a cessie deed for a portion of the receivables before a notary. The making of the cessie deed must be attended by all parties, so that the debtor knows well to whom he must pay. the debt.Keywords: Decision Disparity, Bankruptcy, Cessie AbstrakPutusan pengadilan niaga mengenai permohonan pernyataa pailit dengan dasar cessie atas sebagian jumlah piutang berbeda-beda. Terdapat putusan yang mengabulkan permohonan dan ada juga putusan yang menolak permohonan. Terjadinya perbedaan putusan permohonan pailit dengan dasar yang sama mengakibatkan ketidakak kepastian hukum. Penelitian ini bertujuan untuk mengkaji, menganalisis, dan menjelaskan terjadinya disparitas putusan pengadilan niaga dalam permohonan pailit dengan dasar cessie atas sebagian jumlah piutang serta upaya untuk menghadirkan kepastian hukum. Jenis penelitian hukum normatif dengan pendekatan undang-undang dan pendekatan konseptual. Teknik pengumpulan data dilakukan dengan studi Pustaka. Data yang diperoleh akan dianalisis secara kualitatif. Hasil penelitian menyimpulkan, Pertama, adanya disparitas putusan permohonan pernyataan pailit dengan dasar cessie atas sebagian jumlah piutang terjadi karena adanya perbedaan penafsiran oleh hakim dalam memaknai undang-undang; dan Kedua, upaya untuk menciptakan kepastian hukum dalam permohonan pailit dengan dasar cessie atas sebagian jumlah piutang adalah dengan membuat akta cessie atas sebagian jumlah piutang di hadapan notaris yang wajib dihadiri oleh semua pihak agar debitor mengetahui dengan baik kepada siapa dia harus membayar utangnya.Kata-kata kunci: Disparitas Putusan, Kepailitas, Cessie